Pembelajaran Tahsinul Qiro’ah di Ponpes Miftahussalam Megang Sakti Musi Rawas - Imam Muttaqin (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
This study aims to determine the process of implementing tahsin Qiro’ah in Pon-Pes Miftahussalam Megang sakti Musi Rawas in terms of theory and practice, and the constraints in Qiro’ah tahsin in Pon-Pes Miftahussalam Megang sakti Musi Rawas. This study uses a qualitative approach, with data collection methods, field observations, interviews, and documentation studies. As for the analysis, the writer uses descriptive analysis which aims to explain the characteristics and aspects that are relevant to the observed phenomenon. The results showed that the implementation of Tahsin Al-Qiro’ah in Pon-Pes Miftahussalam Megang sakti Musi Rawas was as follows: (a) The Al-Qur’an Tahsin aims to deepen the theory of the Koran which is related to tajwid, makhorijul letters, characteristics letters, gharaibul Qur’an, and also learning songs to recite Al-Qur’an recitations, (b) Adding to the love of students for the Al-Qur’an. Then the methods applied in the Tahsin Qiro’ah at Pon-Pes Miftahussalam Megang sakti Musi Rawas are: (a) the drill method, (b) the lecture method, (c) the classical reading method. The obstacles in the Qiro’ah tahsin in Miftahussalam Megang sakti Musi Rawas Islamic Boarding School include: (a) lack of tools or visual aids, (b) when Sundays activities are not conducive, (c) lack of understanding of the purpose of tahsin.